The Coal Miners: A Study of Union Control - Karsh, Bernard; London, Jack (Quarterly Journal of Economics, 1954)
Introduction, 415. — I. The structure of control, 416. — II. Appraisal of the union and of Lewis, 419. — III. Attitudes toward provisionalism, 424. — IV. The calling of strikes, 427. — V. Conclusions, 432.